1999
DOI: 10.1021/la9904105
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced States of Orientation of the Lamellar Phase of C12E4/Water

Abstract: The shear-induced states of orientation of the lamellar lyotropic mesophase of tetraethylene glycol monododecyl ether (C12E4) in water are investigated by polarizing microscopy, viscometry, small-angle light scattering, and deuteron NMR spectroscopy. The solution containing 40 w/w % surfactant shows a continuous transition from a state of aligned layers, whose normal is parallel to the velocity gradient, to a close packing of multilamellar vesicles (onion state). The size of the vesicles (diameter d) is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
139
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 46 publications
11
139
1
1
Order By: Relevance
“…Experiments on a variety of systems which differ significantly in their microscopic details show nevertheless striking similarities in their macroscopic behavior under shear. The systems under investigation include block copolymers [1,2,3,4,5,6], low molecular weight (LMW) liquid crystals [7,8,9], lyotropic lamellar phases (both LMW [10,11,12] and polymeric [13]), and liquid crystalline side-chain polymers [14,15]. These experiments use either a steady shear (typically for the low viscosity systems e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on a variety of systems which differ significantly in their microscopic details show nevertheless striking similarities in their macroscopic behavior under shear. The systems under investigation include block copolymers [1,2,3,4,5,6], low molecular weight (LMW) liquid crystals [7,8,9], lyotropic lamellar phases (both LMW [10,11,12] and polymeric [13]), and liquid crystalline side-chain polymers [14,15]. These experiments use either a steady shear (typically for the low viscosity systems e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The common features of all these experiments can be described as follows. Starting with an aligned sample where the layers are parallel to the planes of constant velocity ("parallel" orientation), the layering is stable up to a certain critical shear rate [2,5,8,9,10,11,13]. At higher shear rates two different situations are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Panizza et al [6] found two different regimes in the size changes of MLVs that depended on the initial and final shear rates. Mu¨ller and collaborators [7] reported reversibility in a related system, C 12 E 4 /D 2 O and, in the present work, we investigated the reversibility in the MLV size distribution during stepwise cycling of the shear rate, focusing on the dynamic phase diagram of the system C 10 E 3 / D 2 O described recently by Oliviero et al [32]; where the authors concluded that a steady-state viscosity could be reached independent of the shear history. The very existence of a history-independent steady state under continuous shear is an important issue and in this paper we present a more detailed investigation of this topic.…”
Section: Introductionmentioning
confidence: 82%
“…In fact, many different shear effects have been reported: transformation from lamellar phases to Multi-lamellar vesicles, MLVs (or ''onions''), in different amphiphilic systems and followed by different techniques [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; formation of MLVs in presence of submicron-size particles (''stuffed onions'') [21]; changes in lamellar orientation [17,22,23]; formation of intermediates with cylindrical structure between a lamellar and MLV phases [24][25][26]; reduction in lamellar spacing [27]; transitions from MLVs to unilamellar vesicles [28] and ''layering'' effects on onions [8,29]. As a practical application, these MLVs can be used, for instance, to encapsulate chemicals leading to a new kind of controlled micro-reactor [30] or as carriers for oligonucleotide delivery [31].…”
Section: Introductionmentioning
confidence: 99%
“…We attribute that to already disrupted vesicles in the onion state leading to an increased diffusivity. Correspondingly, planar lamellae may not be completely aligned, 17,57,69 thus reducing the diffusion coefficient in flow direction. This is in agreement with the spectra in Fig.…”
mentioning
confidence: 99%